Exploring the complexities of sand dune transformation: the role of anthropogenic degradation and climatic conditions - Askhat, Naushabayev; Zhu, Kai; Bekzat, Rsymbetov; Tursunay, Vassilina; Nurzikhan, Seitkali; Daniyar, Dosmanbetov; Yersultan, Songulov; Kurmanbek, Zhanymhan; Issakov, Yerlan; Antal, Sándor; Ujj, Apolka; Dávid, Lóránt Dénes (Frontiers in Earth Science, 2023)
Introduction: The sandy soils in the arid Southern Balkhash region have experienced anthropogenic degradation, leading to the formation of bare mobile sand dunes. This transformation has created significant challenges for the growth of cattle feed, particularly in areas with high economic activity. As a consequence, the socio-economic situation of the local population has been significantly worsened, and even the development of tourism has not helped. The objective of this study was to investigate the relationship between the seasonal mobility of sand dune landforms and their hydrothermal regimes, as well as the climatic conditions of the region. Methods: To achieve the study objective, we conducted field investigations and collected data on the mobility of sand dunes, hydrothermal conditions, and climatic factors in the region. Measurements were taken during the summer months when dominant North-East, North-North-East winds prevailed, with an average frequency of 20.4–26.7 days per month and wind speeds ranging from 3.0 to 3.7 m/s, occasionally reaching up to 11.90–13.3 m/s. We also analyzed humidity, air temperature, and atmospheric precipitation levels. Results: Our findings revealed that during the summer months, a fresh-sided layer of sand actively supplied the windward part of the sand dune to the leeward one. This process occurred under very low humidity, high air temperature, and slight atmospheric precipitation conditions. Consequently, the moisture content of the surface root layer (0–20 cm) of the sand dune accumulation zone decreased to 0.2% in the middle and at the end of summer. Discussion: The observed relationship between the seasonal mobility of sand dunes and their hydrothermal regimes, along with the climatic conditions, provides valuable insights for the development of effective technologies to rehabilitate anthropogenically degraded desert sandy soils that have transformed into mobile sands. This knowledge can serve as a theoretical basis for addressing the challenges faced by cattle breeding in the region and improving the socio-economic situation of the local population.